1988
DOI: 10.3758/bf03209036
|View full text |Cite
|
Sign up to set email alerts
|

The rat’s simultaneous anticipation of remote events and current events can be sustained by event memories alone

Abstract: After receiving events in a fixed order, A-B-C... , rats, like people, on being provided with A, may anticipate not only B, a current anticipation, but also C, a remote anticipation. In two experiments, we attempted to determine whether rats' remote anticipations are mediated by item cues (C elicited by A) or by position cues (C directly elicited by Position 3 cues, which generalize to Position 2). In Experiment 1, rats in a runway received two series of three trials, XNY and ZNN, each in irregular order each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
(24 reference statements)
1
24
0
Order By: Relevance
“…Another proposal is that animals learn associations between successive reinforcement magnitudes. For example, rats run more rapidly on a nonreinforced trial that is followed by reinforcement than one that is not (Capaldi & Miller, 1988), suggesting an association between nonreinforcement and the next reinforcement magnitude. Also, Self and Gaffan (1983) found that rats run more rapidly on the third trial ofa repeated ascending 0-1-10 series than a repeated descending 10-1-0 series, demonstrating that performance is not strictly determined by the most recent magnitude (1) or the average magnitude (3.67), and suggesting that performance is influenced by an association between a l-pellet reinforcement and the next reinforcement magnitude (10 or 0).…”
mentioning
confidence: 99%
“…Another proposal is that animals learn associations between successive reinforcement magnitudes. For example, rats run more rapidly on a nonreinforced trial that is followed by reinforcement than one that is not (Capaldi & Miller, 1988), suggesting an association between nonreinforcement and the next reinforcement magnitude. Also, Self and Gaffan (1983) found that rats run more rapidly on the third trial ofa repeated ascending 0-1-10 series than a repeated descending 10-1-0 series, demonstrating that performance is not strictly determined by the most recent magnitude (1) or the average magnitude (3.67), and suggesting that performance is influenced by an association between a l-pellet reinforcement and the next reinforcement magnitude (10 or 0).…”
mentioning
confidence: 99%
“…The very substantial behavioral control exercised by event-generated memories has been demonstrated in partial reinforcement experiments (Capaldi, 1966(Capaldi, , 1971 crimination learning experiments (e.g., Capaldi, Berg, & Morris, 1975;Haggbloom, 1979Haggbloom, , 1981Haggbloom & Tillman, 1980), and recent serial learning investigations (e.g., Capaldi & Miller, 1988;Capaldi & Verry, 1981;Haggbloom, 1985). Haggbloom (1988) reported that the stimulus properties of signal-generated SN, and its capacity to regulate extinction behavior, and event-generated SN were essentially the same.…”
mentioning
confidence: 99%
“…Given the findings of Capaldi and Miller (1988a), then, it is not unreasonable to suggest that when number cues associated with nonreinforcements are confounded with other cues, rats may nevertheless enumerate nonreinforcements. This being so, it follows that animals count when other means of solution are available and that counting reinforcing events may be employed to understand a wide array of learning phenomena (see, e.g., Capaldi, 1964Capaldi, , 1966Capaldi, , 1967Capaldi & Miller, 1988a, 1988b.…”
Section: Resultsmentioning
confidence: 99%
“…Such attributes may be retrieved on some subsequent trial provided the retrieval trial is sufficiently similar to the storage trial (e.g., Capaldi, 1971;Capaldi, Verry, Nawrocki, & Miller, 1984;Jobe, Mellgren, Feinberg, Littlejohn, & Rigby, 1977). Retrieved attributes become signals for the reinforcing event that occurs on the retrieval trial, and thus such attributes function as an anticipatory mechanism (Capaldi & Miller, 1988b;Capaldi, Nawrocki, & Verry, 1983). Vigor of responding is an increasing function of the magnitude of reinforcement signaled by the retrieved attributes.…”
mentioning
confidence: 99%